Accurate determination of phenotypic information from historic thoroughbred horses by single base extension - Campana, M; Whitten, C; Edwards, C; Stock, F; Murphy, A; Binns, M; Barker, G; Bower, M (Public Library of Science, 2010)
Historic DNA have the potential to identify phenotypic information otherwise invisible in the historical, archaeological and palaeontological record. In order to determine whether a single nucleotide polymorphism typing protocol based on single based extension (SNaPshot™) could produce reliable phenotypic data from historic samples, we genotyped three coat colour markers for a sample of historic Thoroughbred horses for which both phenotypic and correct geotypic information were known from pedigree information in the General Stud Book. Experimental results were consistent with the pedigrees in all cases. Thus we demonstrate that historic DNA techniques can produce reliable phenotypic information from museum specimens.